PSYCHOLOGICAL ASPECTS OF LEARNING A FOREIGN LANGUAGE - Esanova Nafosat Faxriddinovna; Akabirova Kamola Malikovna; Yakubova Kamola Shokirovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article considers the issue of taking into account the psychological characteristics of students in the study of a foreign language for professional purposes. It was analyzed the methodological aspects of taking into account psychological features in teaching a foreign language. Emphasis is placed on the need and importance of taking into account the psychological characteristics of students in the process of learning a foreign language for professional purposes.